2008
DOI: 10.1249/mss.0b013e3181641bed
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturation on the Relationship between Muscle Size and Force Production

Abstract: Our results showed that the maximal isometric strength exerted by the forearm muscles in humans is proportional to their size whatever the age, and that VM is the best index of muscle size during growth. The previously reported increased ability to produce maximal strength from childhood to adulthood could be explained by systematic bias introduced by the method used to characterize muscle size instead of physiological or neural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 38 publications
8
95
1
5
Order By: Relevance
“…These contradictory findings might be related to methodological aspects because specific force has been measured differently in the corresponding studies, e.g., with CSA, isolated muscle weight, fiber length, or muscle density (4,6,26) chosen as surrogate markers of muscle volume. By contrast, we quantified muscle volume from multiple MR images, and this technique is considered a gold standard in this field (11,31). Muscle performance impairment reported herein and in previous studies in Mstn-deficient animals warrants further clarification.…”
Section: Nsmentioning
confidence: 90%
See 1 more Smart Citation
“…These contradictory findings might be related to methodological aspects because specific force has been measured differently in the corresponding studies, e.g., with CSA, isolated muscle weight, fiber length, or muscle density (4,6,26) chosen as surrogate markers of muscle volume. By contrast, we quantified muscle volume from multiple MR images, and this technique is considered a gold standard in this field (11,31). Muscle performance impairment reported herein and in previous studies in Mstn-deficient animals warrants further clarification.…”
Section: Nsmentioning
confidence: 90%
“…The setup integrates an ergometer consisting of a foot pedal coupled to a force transducer and two rod-shaped transcutaneous surface electrodes (one located above the knee and the other under the heel) connected to an electrical stimulator (Type 215/T; Hugo Sachs Elektronik-Harvard Apparatus, March-Hugstetten, Germany). The foot was positioned on the ergometer pedal, and the lower hindlimb was centered inside a 20-mmdiameter 1 H Helmholtz imaging coil while the belly of the gastrocnemius muscle was located above an elliptic (8 ϫ 12 mm) 31 P-MRS surface coil. The pedal position was adjusted to modify the angle between the foot and the lower hindlimb so that the gastrocnemius muscle could be passively stretched at rest to produce a maximum isometric twitch tension in response to supramaximal square wave pulses (1.5-ms duration; 2-4 mA).…”
mentioning
confidence: 99%
“…Utilizing differing analytical approaches the reported results with respect to CSA-normalized peak torque are inconsistent (8,25,30,37,47). A few female studies reported the absence of age-related differences in CSA-normalized peak torque (8,31).…”
Section: Discussionmentioning
confidence: 99%
“…While most investigators have found that whole muscle force is proportional to size, it is recognized that the method used to determine muscle size, and possibly age, influence the strength-size relationship (Tonson et al 2008). A mathematical approach somewhat similar to the one we have used has been applied to the relationship between biceps whole muscle size and strength.…”
Section: S Krivickas and Othersmentioning
confidence: 99%